(untitled) (Libellarium: journal for research in the field of information and related sciences, 2017)
The paper presents the issues concerning boosting and promotion of reading in public libraries and focuses on the difference between these two terms used in Croatian practice. Literature review has shown that reading promotion in Croatian public libraries has now been researched enough. The papers on reading deal with specific topics, for example reading habits of different user groups, problems with obligatory readings or importance of reading in general. There are also analyses of PISA and PIRLS results on reading competences. Professional papers usually report on projects and activities on reading promotion. Many of those papers are results of the first national campaign on reading Read to me! Literature review has shown that there are no papers on reading promotion/ marketing written in Croatian. The first part of the paper defines key terms and distinguishes similarities between Croatian meanings of the terms. It also gives an overview of research, projects, non-governmental and professional organizations and societies that are promoting books and reading. The second part of the paper provides results of the research, whose main goal is to present various ways and approaches used in public libraries for book and reading promotion. It also explores how librarians perceive and understand key terms in the field, such as reading promotion, and whether they are aware of the importance of promoting all activities in the library. Research was conducted in the sample of 35 Croatian public libraries recommended by heads of County Research and Development Departments. The librarians were interviewed using the semi-structured interview method. Research results show that librarians often don’t distinguish (or don’t think it’s important to distinguish) between the meanings of the terms used for boosting reading and reading promotion in the Croatian language (Croatian promicanje and promocija) which is why they gave wrong answers to some questions. They usually use Facebook and web sites of libraries to promote activities targeted at younger users and they use the boards in libraries for announcing events and activities targeted at older patrons. Many successful programs go unnoticed by the public because they are not well promoted as most librarians do not have time for promotional activities. Results also point to the necessity of defining important terms in the field of reading promotion, providing education on the evaluation of library projects and activities and raising awareness on the importance of marketing in libraries in general in order to increase visibility in the public and the media.